Spies in the Vatican : espionage & intrigue from Napoleon to the Holocaust - Alvarez, David J. (Modern war studies., 2002)
Revered by millions, the Papacy is an international power that many nations have viewed with suspicion, some have tried to control, and not a few have spied upon. Ranging across two centuries of world history, David Alvarez's fascinating study throws open the Vatican's doors to reveal the startling but little-known world of espionage in one of the most sacred places on earth. Reviewing the pontificates of ten popes-from Pius VII, Napoleon's nemesis, to Pius XII, maligned by some as "Hitler's pope"--Alvarez provides the first history of the intelligence operations and covert activities that reac